Subacute THYROiditis related to SARS-CoV-2 VAccine and covid-19 (THYROVAC Study): A multicenter nationwide study - BOSTAN, HAYRİ; İMRE, EREN (My University, 2023)
CONTEXT: The aims of the study are to compare characteristics of subacute thyroiditis (SAT) related to different etiologies, and to identify predictors of recurrence of SAT and incident hypothyroidism. METHODS: This nationwide, multicenter, retrospective cohort study included 53 endocrinology centers in Turkey. The study participants were divided into either COVID-19-related SAT (Cov-SAT), SARS-CoV-2 vaccine-related SAT (Vac-SAT), or control SAT (Cont-SAT) groups. RESULTS: Of the 811 patients, 258 (31.8%) were included in the Vac-SAT group, 98 (12.1%) in the Cov-SAT group, and 455 (56.1%) in the Cont-SAT group. No difference was found between the groups with regard to laboratory and imaging findings. SAT etiology was not an independent predictor of recurrence or hypothyroidism. In the entire cohort, steroid therapy requirement and younger age were statistically significant predictors for SAT recurrence. C-reactive protein measured during SAT onset, female sex, absence of antithyroid peroxidase (TPO) positivity, and absence of steroid therapy were statistically significant predictors of incident (early) hypothyroidism, irrespective of SAT etiology. On the other hand, probable predictors of established hypothyroidism differed from that of incident hypothyroidism. CONCLUSION: Since there is no difference in terms of follow-up parameters and outcomes, COVID-19- and SARS-CoV-2 vaccine-related SAT can be treated and followed up like classic SATs. Recurrence was determined by younger age and steroid therapy requirement. Steroid therapy independently predicts incident hypothyroidism that may sometimes be transient in overall SAT and is also associated with a lower risk of established hypothyroidism.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; ENDOKRİNOLOJİ VE METABOLİZMA; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MOLECULAR BIOLOGY & GENETICS; ENDOCRINOLOGY & METABOLISM; BIOCHEMISTRY & MOLECULAR BIOLOGY; Endokrinoloji, Diyabet ve Metabolizma; Endokrinoloji; Klinik Biyokimya; Biyokimya (tıbbi); Endocrinology, Diabetes and Metabolism; Endocrinology; Clinical Biochemistry; Biochemistry (medical); COVID-19; SARS-CoV-2 vaccine; subacute thyroiditis